Modulation of urelumab glycosylation separates immune stimulatory activity from organ toxicity - Reitinger, Carmen; Ipsen-Escobedo, Andrea; Hornung, Chiara; Heger, Lukas; Dudziak, Diana; Lux, Anja; Nimmerjahn, Falk (Frontiers in Immunology, 2022)
Checkpoint control and immunomodulatory antibodies have become important tools for modulating tumor or self-reactive immune responses. A major issue preventing to make full use of the potential of these immunomodulatory antibodies are the severe side-effects, ranging from systemic cytokine release syndrome to organ-specific toxicities. The IgG Fc-portion has been demonstrated to contribute to both, the desired as well as the undesired antibody activities of checkpoint control and immunomodulatory antibodies via binding to cellular Fc-receptors (FcR). Thus, choosing IgG subclasses, such as human IgG4, with a low ability to interact with FcRs has been identified as a potential strategy to limit FcR or complement pathway dependent side-effects. However, even immunomodulatory antibodies on the human IgG4 background may interact with cellular FcRs and show dose limiting toxicities. By using a humanized mouse model allowing to study the immunomodulatory activity of human checkpoint control antibodies in vivo, we demonstrate that deglycosylation of the CD137-specific IgG4 antibody urelumab results in an amelioration of liver toxicity, while maintaining T cell stimulatory activity. In addition, our results emphasize that antibody dosing impacts the separation of side-effects of urelumab from its therapeutic activity via IgG deglycosylation. Thus, glycoengineering of human IgG4 antibodies may be a possible approach to limit collateral damage by immunomodulatory antibodies and allow for a greater therapeutic window of opportunity.